Hydatidosis: Case report and literature review (Indian Journal of Case Reports, 2020)
Hydatid cyst (HC) or hydatidosis is a global parasitic zoonosis infection caused by the larval stage of cestode Echinococcus granulosus. It continues to be a substantial cause of morbidity and mortality in many parts of the world, endemic to countries in the Mediterranean, Australia, North Africa, Australia, New Zealand, South America, the Philippines, Northern China, and the Indian subcontinent. Hydatid disease is endemic in India. We report the case of a HC of the liver with multiple abdominal HCs in a 61-year-old female with complaints of multiple painless lumps in the abdomen which was gradually increasing in size. A contrast-enhanced CT scan of the abdomen and pelvis was done with findings suggestive of HC of the liver with multiple peritoneal hydatidoses. Treatment strategies of HC of the liver can include medical therapy, percutaneous drainage, or surgical intervention (through a conventional or laparoscopic approach).